Cardiac Rehabilitation in a Young Patient with Severe Left Ventricular Dysfunction and Stroke: a Case Study - Correa, Margarita; Padró, Carmen A.; Lugo, Marie C.; Micheo, William (Puerto Rico Health Sciences Journal, 2014)
see manuscript